Exploring Students’ Mathematical Reasoning Through Discovery Learning with Gamification Media on the Pythagorean Theorem - Alfi Syahrin Siregar; Toto Nusantara; Erry Hidayanto (Universitas Suryakancana, 2026)
Reasoning is an important foundation in solving mathematical problems. Reasoning is a thinking process that allows students to understand concepts, connect ideas, and draw logical conclusions. This study aimed to explore students’ mathematical reasoning in Discovery Learning supported by gamification media on the Pythagorean Theorem. The study used a qualitative case study approach involving two eighth-grade students at a junior high school in Malang. Data were obtained through observation, interviews, and mathematical reasoning tests, then analyzed using the Miles and Huberman model. The findings revealed that Discovery Learning, supported by gamification media, created an interactive learning experience that enabled students to gradually explore concepts in context. High-ability students demonstrated strong reasoning skills, including analyzing problems, constructing arguments, applying inductive and deductive reasoning, making generalizations, and drawing conclusions. Low-ability students also showed improvement in several reasoning indicators, particularly in analyzing problems, applying deductive reasoning, and developing mathematical arguments during the learning process. Keywords: Reasoning, Discovery Learning, Gamification, Pythagorean Theorem